Development of theory of the drive of stationary agricultural machines with lever mechanisms - Bulgakov, Volodymyr; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич (My University, 2019)
The improvement of the efficiency of agricultural machines of a modern technical level can be achieved when new methods of the theory of mechanisms and machines are used during calculations and design of their working bodies and in general of machine aggregates. The task of the research was to develop a new algorithm for solving the second problem of dynamics of lever mechanisms with electric drive, which are used in modern agricultural machines A new algorithm for solving the second problem of dynamics of lever mechanisms of agricultural machines equipped with an electric drive has been developed. The algorithm finds application in calculations of flat lever mechanisms of stationary agricultural machines.
Keywords: lever mechanism; resistance forces; moment of inertia; flywheel; algorithm; calculation